PENINGKATAN BERAT BADAN BAYI MELALUI KELAS PIJAT UNTUK USIA 1-6 BULAN: PROGRAM PENGABDIAN MASYARAKAT - Ella, Lailaturohmah; Restya Agustin, Erda (Stikes Yarsi Mataram, 2024)
Increasing infant weight is an important indicator of optimal growth and development. One effective method to achieve this is through baby massage, which can provide both physical and psychological stimulation for the infant. This community service activity aims to increase the weight of infants aged 1-6 months through baby massage classes conducted at Posyandu Perumahan Griya Intan Asri, Mrican, Kota Kediri. The program involved 10 mothers with infants aged 1-6 months as participants. The methods used included socialization, education, and training in baby massage techniques by competent healthcare professionals. The training provided practical guidance on safe and effective baby massage techniques to enhance infant weight and well-being, as well as to strengthen the bond between mother and child. The results of the program showed that out of the 10 infants who participated, 8 infants (80%) experienced weight gain after the baby massage sessions, while 2 infants (20%) maintained their weight. None of the infants experienced weight loss. These results indicate that baby massage classes have a significant impact on increasing infant weight, which is a crucial indicator for their optimal growth and development. Therefore, this baby massage class program can be considered effective in improving both the physical and psychological health of infants and strengthening the role of mothers in caregiving to support their children's optimal growth and development